(untitled) (FUDMA JOURNAL OF SCIENCES, 2023)
Adsorption of malachite green (MG) dye onto defatted papaya seeds (DPS) was studied. Effects of initial dye concentration, contact time, pH and the solution temperature were investigated. It was found that adsorption of malachite green onto the defatted Carica papaya seeds was favorable in the acidic medium while the adsorption uptake increased with increasing initial dye concentration, solution temperature and contact time. Isotherm models such as Langmuir, Freundlich, and Temkin were used to analyze the data and Langmuir isotherm was found to be the best fit for the adsorption data with a monolayer adsorption capacity of 126.05 mg/g. The adsorption study showed that defatted papaya seed could be a viable alternative adsorbent in the removal of potentially toxic dyes from aqueous solution